A Vision for Nepal : Policy Notes for the Government, Volume 1. Synthesis Report - World Bank Group (Washington, DC, 2014)
Nepal needs a new economic model to achieve faster and sustained growth as well as further improvements in human development and poverty outcomes. Economic growth, while ro¬bust at around 4 percent annual average since 2005, is far from the level needed to achieve the government s ambitious targets. The economy, highly dependent on remittances, lacks the nec¬essary dynamism. While substantial gains have been made to reduce poverty and expand access to services, achieving further progress will require more determined and targeted state intervention. To redefine Nepal s growth model, public policy should focus on 3 I s: Investment, In¬frastructure, and Inclusion. Investment is the bedrock of a sustainable growth model but in Nepal, the state, firms and households critically under-invest, with gross fixed capital formation between 19.9 and 22.2 percent of GDP over the past decade (compared to 30 percent or more in fast-growing countries in East Asia). In order to unlock investment as well as to expand access to services and opportunities for all, public infra¬structure is critical, but Nepal is under-connected and under-powered. Finally, growth alone will not deliver continued fast progress on inequality and poverty reduction unless the growth model is calibrated for inclusion, which in turn can help sustain dynamic growth.